Liberalizing art: Evidence on the impressionists at the end of the Paris Salon - Federico Etro; Silvia Marchesi; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
We analyze the Paris art market between the government-controlled Salon as a centralized organization of art exhibition and the system liberalized by the Republican government based on competition between independent exhibitions. The jury of the old Salon decided on submissions with a bias toward conservative art of the academic insiders, reducing demand for the outsiders, as confirmed by the impact on prices of the acceptance of Impressionists. With a difference-in difference estimation we provide evidence that the end of the government-controlled Salon in 1880 started the increase of the prices of the Impressionists relative to the insiders.
Keywords: C23; Z11; 330; Art market; Market structure; Insider-Outsider; Hedonic regressions; Impressionism